Acceptance and practices of cash WAQF among university’s students - Nasiri, Abdulrahim; Noori, Abdullah; Che Mohd Salleh, Marhanum (Human Resource Management Academic Research Society, 2019)
Innovation in Waqf (Islamic endowment) in the modern century has made movable asset like cash Waqf practices possible. This research further examines the awareness, acceptance, and practices of cash Waqf among university students. Other objective is to evaluate their perception towards the management of cash Waqf in Malaysia. To achieve the objectives, primary data were collected through survey among 160 International Islamic University Malaysia (IIUM) students. Based on few statistical analyses, results revealed that even though IIUM students have moderate level of awareness towards cash Waqf, they were basically have high level of acceptance and practices towards the implementation of cash Waqf in the country. Hence, cash Waqf practices should be continued and innovate for future benefits to the society.